2023
DOI: 10.1002/hbm.26513
|View full text |Cite
|
Sign up to set email alerts
|

Somatotopic disruption of the functional connectivity of the primary sensorimotor cortex in complex regional pain syndrome type 1

Jaakko Hotta,
Jukka Saari,
Hanna Harno
et al.

Abstract: In complex regional pain syndrome (CRPS), the representation area of the affected limb in the primary sensorimotor cortex (SM1) reacts abnormally during sensory stimulation and motor actions. We recorded 3T functional magnetic resonance imaging resting‐state data from 17 upper‐limb CRPS type 1 patients and 19 healthy control subjects to identify alterations of patients' SM1 function during spontaneous pain and to find out how the spatial distribution of these alterations were related to peripheral symptoms. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 103 publications
0
4
0
Order By: Relevance
“…Prior research has identified abnormalities in rsFC within multiple brain networks in patients with CRPS. These networks include the fronto-parietal [ 4 , 6 ], motor [ 3 , 7 , 10 ], somatosensory [ 5 , 6 , 11 ], subcortical [ 3 , 6 , 10 , 11 ], salience [ 4 , 8 , 9 ], central executive [ 4 ], and default mode [ 4 , 5 ] networks. These brain network alterations can be classified into two broad categories.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Prior research has identified abnormalities in rsFC within multiple brain networks in patients with CRPS. These networks include the fronto-parietal [ 4 , 6 ], motor [ 3 , 7 , 10 ], somatosensory [ 5 , 6 , 11 ], subcortical [ 3 , 6 , 10 , 11 ], salience [ 4 , 8 , 9 ], central executive [ 4 ], and default mode [ 4 , 5 ] networks. These brain network alterations can be classified into two broad categories.…”
Section: Discussionmentioning
confidence: 99%
“…These brain network alterations can be classified into two broad categories. The first category includes abnormalities in pain sensation [3][4][5][6][7][8][9]11] and cognitive-emotional changes [6,8]. The second involves limb movement disorders such as dystonia [3,4,10].…”
Section: Crps Phenotypes and Rsfcmentioning
confidence: 99%
See 2 more Smart Citations